Một số nguyên nhân gây lỗi trong dịch văn bản chính luận Trung - Việt /Nguyễn Thị Minh. - Nguyễn, Thị Minh.
The article analyzes several reasons leading to the mistranslation of Chinese Vietnamese political documents through specific examples such as misunderstanding the source texts, incorrect expressions, not reviewing the translations, not paying attention to the external factors, etc.